2011
DOI: 10.1371/journal.pone.0022662
|View full text |Cite
|
Sign up to set email alerts
|

A Double Blind, Placebo-Controlled, Randomized Crossover Study of the Acute Metabolic Effects of Olanzapine in Healthy Volunteers

Abstract: Background and RationaleAtypical antipsychotics exhibit metabolic side effects including diabetes mellitus and obesity. The adverse events are preceded by acute worsening of oral glucose tolerance (oGTT) along with reduced plasma free fatty acids (FFA) and leptin in animal models. It is unclear whether the same acute effects occur in humans.Methodology/Principal FindingsA double blind, randomized, placebo-controlled crossover trial was conducted to examine the potential metabolic effects of olanzapine in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
71
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 44 publications
14
71
4
Order By: Relevance
“…We observed this previously with olanzapine in rodents, 11,13 and in humans FFA lowering is also observed. 10,12,17 SGAs have a very short half-life in rodents, so it is tempting to speculate that with longer exposures facilitated by higher doses, plasma concentrations of FFA may reach a critical concentration that is insufficient to maintain energy requirements leading to the observed drops in the VO 2 at higher SGA doses. It does not seem likely that the VO 2 lowering is secondary to sedation because decreased physical activity was also observed in animals treated with aripiprazole, which did not affect VO 2 , and ANCOVA testing failed to reveal an interaction between these variables after any treatment.…”
Section: Cpt-1 Inhibitors and Sgasmentioning
confidence: 99%
See 3 more Smart Citations
“…We observed this previously with olanzapine in rodents, 11,13 and in humans FFA lowering is also observed. 10,12,17 SGAs have a very short half-life in rodents, so it is tempting to speculate that with longer exposures facilitated by higher doses, plasma concentrations of FFA may reach a critical concentration that is insufficient to maintain energy requirements leading to the observed drops in the VO 2 at higher SGA doses. It does not seem likely that the VO 2 lowering is secondary to sedation because decreased physical activity was also observed in animals treated with aripiprazole, which did not affect VO 2 , and ANCOVA testing failed to reveal an interaction between these variables after any treatment.…”
Section: Cpt-1 Inhibitors and Sgasmentioning
confidence: 99%
“…In contrast, olanzapine does not increase glycerol rates of appearance in humans 17 despite causing glucose intolerance within days. 12 Furthermore, in both acute and chronic preclinical studies, basal and isoproterenolstimulated lipolyses were actually impaired in vivo by olanzapine. 13 From an energy-balance standpoint, increasing reliance on fat as a fuel while not increasing lipolysis would seem to be a potentially unsustainable situation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…chotics has not been studied thus far. Several studies have shown decreased plasma concentration of HDL-cholesterol in subjects treated with SGAs for a long term ( 10,46,47 ). Whether the change in ABCA1 gene expression induced by antipsychotics contributes to the reduction of HDL-cholesterol levels is not known; more detailed studies are required to elucidate this important issue.…”
mentioning
confidence: 99%